Biomass yield and energy potential of short-rotation energy plantations of Gmelina arborea one year old in Costa Rica - Arias-Aguilar, Dagoberto; Briceño-Elizondo, Elemer; Tenorio-Monge, Carolina; Moya-Roque, Róger (Elsevier, 2016)
Short-rotation woody plantations have been recently established in Costa Rica and Gmelina arborea has gained popularity The present work assesses tree diameter and height, biomass distribution, specific gravity, green density, moisture content, calorific value, ash content, volatile materials, carbon, nitrogen, extractives and production of energy in one-year-old short-rotation energy plantations of G. arborea in three different sites in Costa Rica, planted under three spacings (0.5 × 0.5 m, 1.0 × 1.0 m and 2.0 × 2.0 m). The results showed that the properties evaluated presented little variation due to spacing. The variations by site and spacing in the properties of the biomass and its characteristics could be easily observed by multivariate analysis. According to this analysis, one site excelled with the best energy characteristics, while spacings of 0.5 × 0.5 m and 1.0 × 1.0 m show higher energy and biomass production in the three sites. Regarding the study of the characteristics and distribution of biomass in different parts of the tree, differences were found in initial moisture content, calorific value and volatile materials between the trunk, branches or bark. The highest percentage of biomass is concentrated in the trunk and branches. Finally, it was concluded that the species G. arborea produces similar amounts of biomass compared to other short-rotation energy crops.
Artículo científico
Keywords: Bioenergía; Leña; Energía; Plantaciones; Arboles; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING